2019
DOI: 10.1177/0961203318820707
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor gene polymorphisms and serum angiotensin-converting enzyme level in Egyptian children with systemic lupus erythematosus

Abstract: Background There are no reports about the association of angiotensin II type 2 receptor (AT2R) gene polymorphisms and susceptibility to systemic lupus erythematosus (SLE) in children. Objective The objective of this research is to study AT2R gene polymorphisms in exon 3 (C1593A) and intron 1 (A1675G) in Egyptian children with SLE and its correlation with disease manifestations and serum angiotensin-converting enzyme (ACE) level. Methods Typing of AT2R gene polymorphisms was conducted in 123 children with SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…The gene encoding the type 2 angiotensin II (Ang II) receptor ( AGT2R ) plays a pivotal role in atherosclerosis, vascular inflammation, and remodeling and has anti-inflammatory and antiproliferative influences, and it exhibited a female advantage by counteracting the AT1 receptor in mice ( 46 ). In SLE, AGT2R polymorphisms containing the A allele (CA + AA) in exon 3 or G allele (AG + GG) in intron 1 are of apparent significance compared with HC ( 47 ). AGT2R expression is also strongly enhanced in RA synovial tissue, an exogenous agonist that could ameliorate inflammation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding the type 2 angiotensin II (Ang II) receptor ( AGT2R ) plays a pivotal role in atherosclerosis, vascular inflammation, and remodeling and has anti-inflammatory and antiproliferative influences, and it exhibited a female advantage by counteracting the AT1 receptor in mice ( 46 ). In SLE, AGT2R polymorphisms containing the A allele (CA + AA) in exon 3 or G allele (AG + GG) in intron 1 are of apparent significance compared with HC ( 47 ). AGT2R expression is also strongly enhanced in RA synovial tissue, an exogenous agonist that could ameliorate inflammation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…[31] The minimum level of statistical significance was adjusted at p-value less than 0.05. [32] 3 | RESULTS…”
Section: Discussionmentioning
confidence: 99%
“…The AT1R gene [92] and AT2R gene [93] polymorphisms might be considered as potential risk factors for children from Egypt with SLE [92,93]. Shoaib et al [92] hypothesized that the AT1R gene polymorphism observed in SLE patients reduces the regulatory effect of miRNA155 on AT1R gene expression, leading to high levels of AT1R.…”
Section: Lupus Erythematosus (Le)mentioning
confidence: 99%
“…Further studies made by Shoaib et al [93] in Egyptian children marked the first exploration of the relationship between AT2R gene polymorphisms and SLE susceptibility. In SLE, the processes of clearance and/or apoptosis could be unstable.…”
Section: Lupus Erythematosus (Le)mentioning
confidence: 99%
See 1 more Smart Citation